Dr. Matthew Yeo — Deep Plane Facelift — Singapore - Yeo, Matthew (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Matthew Yeo, practicing in Singapore, Singapore. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003231; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; singapore; singapore